SOME CONSIDERATIONS ON THE POLITICAL ACTIVITIES OF SARA HATUN, THE FIRST DIPLOMAT IN TURKISH-ISLAMIC HISTORY - Şemşek, Vesile (The Journal of Social Science, 2020)
ABSTRACT During the history of Turkic politics, it is observed Turkic women close interaction in external and internal issues of the government and their huge impact on state policy. Primarily, mothers, wifes, sisters of rulers had more chance in participation of the matters regarding state politics and diplomatic relations. Their official political satatus is obvious as a matter of fact that these women’s names were printed on edicts, records, and inscriptions. Sara hatun, who is one of the prominent women in state affairs in the historical scene, continued her activities in political and administrative life with her strong-willed, intelligent and intelligent political moves and patronizing attitude. As a Turkish Muslim lady, she left her mark in the history of statism through her political activities. Thus, it is useful to examine the active roles of a Turkmen chick who can successfully maintain historical traditions as well as her political personality in state politics. In this study, we try to reveal the political and cultural activities of Sarah Hatun, who has distinguished role in turkic political history with her important contributions to the history of diplomacy, as well as to benefit from counciousness of these historical contributions.
Keywords: sara hatun; political aktivitiest; türkish-ıslamıc; history; akkoyunlu state; 5. Gender equality; 16. Peace & justice